Catherine Perlès. Ornaments and other ambiguous artifacts from Franchthi, Volume I, the Palaeolithic and the Mesolithic, excavations at Franchthi Cave, Greece - Galanidou, Nena (Journal of Greek Archaeology, 2019)
Under the modest heading of a fascicle, the 15th volume of the Excavations at Franchthi Cave publication series is entitled Ornaments and Other Ambiguous Artifacts from Franchthi and is authored by Catherine Perlès. Unlike her previous studies of the knapped stone artifacts that were delivered in French, this work is written in English and will be valuable to a wide audience of specialists and students. The work at hand is one more welcome addition to the impressive series published by Indiana University Press, which is unparalleled in the archaeological literature of Stone Age Greece and southeast Europe in terms of quantity, quality and detail of publication. Thanks are due to the wise ‘Franchthi board’ who carry on the legacy of the site and its excavation in the 21st century (and perhaps to the excavator Tom Jacobsen who sends his jazzy blessings from the sky).